Molecular beacon-based temperature control and automated analyses for improved resolution of melting temperature analysis using SYBR I green chemistry. - Nellåker, C; Wållgren, U; Karlsson, H (2007)
BACKGROUND: Melting temperature analysis of products amplified with SYBR I Green chemistry is a cheap and effective method for identification of sequence differences. When used in conventional quantitative real-time PCR instruments (qPCR), this method is limited by temperature variations over the heating block and low numbers of fluorescence measurements during the dissociation step, which hamper the ability of most instruments to report accurate and precise melting temperatures. METHODS: We designed a molecular beacon-based temperature indicator probe (Tm-probe) to control for variations in temperatures over the heating block of the instrument. In addition, we wrote an automated curve-fit analysis algorithm of dissociation data to use multiple data points with a gaussian curve fit to extrapolate precise melting temperatures. RESULTS: Use of the Tm-probe in conjunction with the analysis algorithm and multiple dissociations improved SDs of melting temperatures over a 96-well plate from 0.19 to 0.06 degrees C. CONCLUSIONS: Melting temperature analyses with SYBR I Green chemistry on conventional qPCR instruments can be improved by the use of a Tm-probe in conjunction with curve-fit analysis of data. Resolution improvement up to 3-fold is possible and allows additional melting temperatures to be identified.